Complex mineralogical-geochemical sequences and weathering events in the supergene ore of the Cu–Co Luiswishi deposit (Katanga, D.R. Congo). (January 2020) - Fontaine, Laurent; De Putter, Thierry; Bernard, Alain; Decrée, Sophie; Cailteux, Jacques; Wouters, Johan; Yans, Johan
Abstract: The Luiswishi Cu–Co ore deposit (Haut-Katanga, D.R. Congo) belongs to the Katanga Copperbelt (KCB), a world-class Cu–Co district. The primary orebodies in the KCB consist of sulphide ore hosted in Neoproterozoic fine-grained siliciclastic and carbonate sedimentary rocks. The secondary weathered ores are still poorly documented, though most of them are strongly enriched in both copper and cobalt with regard to the primary sulphide ores. Combined mineralogical (transmitted and reflected light microscopy, XRD, SEM-EDX) and geochemical investigations (FUS-MS and FUS-ICP) on both host rocks and ore minerals allow identifying and characterizing three distinct zones in the studied profile, at Luiswishi, from base to top: the protore, which contains sulphides and massive dolomite; the cementation zone where oxides and sulphides coexist, and the saprolite, comprised of oxidized ores only. The mixed oxidized-sulphide zone occurs down to about 100 m in depth. At Luiswishi, the formation of the oxidized ores proceeded as follows: (1) oxidation of the primary sulphides (mainly chalcopyrite, carrollite and pyrite); (2) rapid neutralization of the released acidity by carbonate minerals (mainly dolomite) and Mg-chlorite in the host rock; and (3) concomitant precipitation of a wide range of oxidized mineral phases: goethite, malachite, heterogenite, pseudomalachite, amorphous copper silicate compound. Complex geometries and recurring mineralogical successions within heterogenite – malachite, or malachite – copper silicate – malachite aggregates are highlighted in the weathering profile. Mineralogical transformations in the weathered profile result in an overall selective leaching of the LREE and a concomitant residual enrichment in HREE. The leached LREE accumulate in the cementation zone, where both secondary chalcocite-type sulphides and residual and replacement goethite form, by oxidation within the rims and cracks in chalcopyrite. Deriving from a specific protore, the oxidized S.D.1b (formerly "Black Ore Mineralized Zone" or B.O.M.Z.) shows a specific geochemical response to weathering, with enrichment in both LREE and HREE and positive Ce-anomaly in the saprolite. Highlights: Detailed study of a weathering profile on supergene ore in the Katanga Copperbelt. No mineralogical type sequence for Cu–Co crystallization during weathering. Thorough discussion of the fractionation and mobility of REE during weathering.